News framing of avian flu: Media advocacy and response to a public health crisis. (December 2019) - Choi, Minhee; McKeever, Brooke Weberling
This study explores how South Korean newspapers reported the issue of AI (avian influenza) by employing framing, and the concepts of media advocacy and mobilizing information (MI). Results indicate that news stories were more likely to attribute blame to the government. Government, scientist/researcher, and farmer sources were most prevalent in news coverage. Mentions of tactical MI for the preventive actions increased. Overall, findings indicate the increased media advocacy efforts during repetitive outbreaks of AI.